Caracterización de la carga de combustible forestal muerto y su inflamabilidad en la Quinta Experimental Punzara de la Universidad Nacional de Loja - Gaona Delgado, Melanny Arianys (2025)
Wildfires are a critical disturbance in ecosystems, influencing successional dynamics, biodiversity, and nutrient cycling. Forest plantations play an important role in this context, providing economic and productive benefits for local communities and the timber industry. However, poorly managed plantations can become vulnerable to fire due to the accumulation of substantial plant fuels, endangering their ecological and economic functions. Therefore, studies that quantify forest fuel load and assess flammability in these plantations are essential for identifying potential risks and preventing adverse socio-environmental impacts. This study characterized the dead forest fuel load at Quinta Punzara, part of the National University of Loja, and evaluated its flammability under controlled conditions. Ten 5 × 20 m plots and two 50 × 50 cm subplots were established to estimate moisture content and assess the floristic composition of the understory. Fuel characterization involved conducting transects in each plot, following Brown's methodology to classify dead plant material. Branch and litter samples were collected and dried in the Plant Physiology Laboratory. Flammability analysis used the direct flame method, with 15 repetitions per fuel type, measuring ignition time, sustainability, combustibility, flame height, and calculating a flammability index. Pappobolus acuminatus and Viburnum triphyllum were the most abundant species among the 64 species identified in the plantation understory. The total dead forest fuel load was 33.16 Mg ha⁻¹, with fine fuels being the predominant component. Litter had the highest moisture content (0.39). Flammability tests yielded an average ignition time of 43.38 s, sustainability of 112.3 s, combustibility of 0.063 g/s, and flame height of 16.57 cm, classifying the dead forest fuel as highly flammable. Understanding the different categories of dead forest fuel and their flammability is crucial for reducing wildfire risks in plantations, especially since fine branches contribute significantly to the fuel load, making these areas susceptible to fire disturbances.